Effective teaching and optimal experiences: possible link - Cardoso, Francisco (2012)
ABSTRACT: Although the link between the occurrence of optimal experiences and successful learning had already been studied in the field of music education, the link between effective teaching and optimal experiences had not yet been systematically studied. For this study, 14 instrumental teachers were interviewed, and the narrative of seven of them (who had reported frequent optimal experiences while teaching) was analysed against Collinson’s model of effective teaching. The narrative of those seven teachers included several references to the three levels of knowledge of Collinson’s model (professional, interpersonal and intrapersonal), showing that a link between effective teaching and optimal experiences may in fact exist.